IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT THROUGH ANAGRAM TECHNIQUE IN SMP N I BANDAR - Desi Junika; Elia Masa Gintings (Universitas Negeri Medan, 2013)
ABSTRACT This study attempts to improve students’ vocabulary achievement through anagram technique. This research was conducted by using action research method. The subject of this study was grade VIII students of SMP N I Bandar. The number of the students was thirty one students, consisted of ten boys twenty one girls. They were taught through anagram technique. The instrument used were vocabulary tests, diary notes, interview sheet, questionnaire sheet and observation sheet. The technique of data analysis were quantitative and qualitative. In analyzing the data, the mean of the students’ score for the first vocabulary test as orientation was 38,70, for the second vocabulary test as a cycle I test was 66,29, for the third vocabulary test as cycle II test was 82,74. The total percentage of the improvement from the first reading test to the third reading test was 7,12%. The conclusion is that anagram technique can improve the students’ vocabulary achievement. The qualitative data show that the students were more interested and motivated on vocabulary achievement through anagram. It is suggested that teachers should apply anagram technique as one of methods to improve students’ achievement in vocabulary. Keywords: Anagram technique, Action research